RESPON SISWA TERHADAP PENGGUNAAN WEBSITE QUIZWHIZZER SEBAGAI MEDIA PEMBELAJARAN DALAM KELAS - Filaili Ainun Jariyah; Raras Hafiidha Sari; Abdul Ghofur (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to find out the students' opinions on the use of the QuizWhizzer and Wordwall websites for completing assignments in class, and it seeks to describe the students' responses regarding the ease of use of QuizWhizzer. Describing the influence of QuizWhizzer on students' learning motivation. Describing the challenges faced by students in using QuizWhizzer. This type of research is descriptive qualitative research. The descriptive qualitative method was chosen to analyze research objects that cannot be measured with numbers. The reason the researcher used this method is that it is suitable for explaining students' responses to the use of the QuizWhizzer website as a learning medium. Researchers collected data through observations and questionnaires, along with interviews with eleventh-grade students. The results of this study indicate that many students provided positive feedback regarding the use of the QuizWhizzer website as a medium for classroom learning activities. The results of this study are useful as a reference for future research on other groups of students, such as those with different learning styles or students with varying academic abilities